2011
DOI: 10.5194/hess-15-3689-2011
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-physical processes at the plunge point: an analysis using satellite and in situ data

Abstract: Abstract. The plunge point is the main mixing point between river and epilimnetic reservoir water. Plunge point monitoring is essential for understanding the behavior of density currents and their implications for reservoir. The use of satellite imagery products from different sensors (Landsat TM band 6 thermal signatures and visible channels) for the characterization of the river-reservoir transition zone is presented in this study. It is demonstrated the feasibility of using Landsat TM band imagery to discer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…However, sporadic heavy rain may occur in the region, mixing the entire water column of the reservoir. Studies made in the Manso reservoir during the same period of our sampling (Assireu et al, 2011; Pacheco et al, 2011) reported a plunge inflow of the river Manso in the reservoir, allocating the river at the hypolimnion level. This inflow of the Manso River in the reservoir highlights possible interactions between the river water and the POM pools in hypolimnion of the dam zone.…”
Section: Discussionmentioning
confidence: 56%
“…However, sporadic heavy rain may occur in the region, mixing the entire water column of the reservoir. Studies made in the Manso reservoir during the same period of our sampling (Assireu et al, 2011; Pacheco et al, 2011) reported a plunge inflow of the river Manso in the reservoir, allocating the river at the hypolimnion level. This inflow of the Manso River in the reservoir highlights possible interactions between the river water and the POM pools in hypolimnion of the dam zone.…”
Section: Discussionmentioning
confidence: 56%
“…During the rainy season in the Funil Reservoir, due to the substantial difference between the river and reservoir surface temperatures (∼ 4 • C), the river water progressively sinks down (underflow) and contributes to the thermal stability of the water column (Fig. 5a, Assireu et al, 2011). The denser river water flows under the lighter reservoir water and waves and billows develop along the interface due to the shear velocity.…”
Section: Physical Features and Spatial Distributionmentioning
confidence: 99%
“…The inflow water with sediments, was heavier and colder than the reservoir water, thus it plunged into the water column in reservoir and became an 25 underflow (turbid flow). The reservoir surface was less affected by the underflow and maintained a relatively stable emission rate (F. as continued water discharging allowed little time for mineralization of organic carbon (Assireu et al, 2011;Senturk, 1994). But in the dry season, the clean inflow water was lighter than the reservoir water, thus it joins the reservoir as surface flow.…”
Section: Damming Effect On Carbon Evasion In the Upper Mekong Rivermentioning
confidence: 99%